An Islamic-Based Spiritual Competence Instrument for Madrasah Teachers: Psychometric Validation Using Rasch Analysis - Firdaos, Rijal; Rohmatul Uyuni, Yuyun; Muhajir; Romlah; Setiawan, Ferdi (Jurnal Pendidikan Agama Islam, 2026)
Purpose – Spiritual competence is an important aspect of the teaching and learning process. This study aims to evaluate the psychometric properties of a spiritual competence instrument for madrasah teachers, including its unidimensionality, local independence, item fit, and reliability. The instrument consists of three dimensions: ulul albab, akhlakul mahmudah, and tasamuh, and was analyzed using the Rasch model. Design/methods/approach - This study employed Gable's affective instrument development approach. The sample comprised 375 madrasah teachers, including 177 male and 198 female teachers. Using a multistage cluster sampling technique, participants were drawn from four major cluster areas in Banten Province: Tangerang Regency, Serang City, Pandeglang Regency, and Cilegon City. Data were analyzed using the Rasch model, including tests of unidimensionality, local independence, item fit, Wright map analysis, reliability testing, and item information function analysis. Findings – Empirical findings based on the Rasch model confirmed that the items measuring the spiritual competence of madrasah teachers were valid and reliable across the three dimensions. The results showed that 20 of the 23 items met the fit criteria (MNSQ: 0.5–1.5; PTMEA: > 0.40). The item reliability was 0.99 (excellent), respondent reliability was 0.76 (moderate), and Cronbach's alpha was 0.77. The Rasch model explained 44.2% of the total raw variance, while the first contrast in the unexplained variance accounted for only 7.1%, which is below the 15% threshold for unidimensionality. Research implications/limitations – Although the instrument demonstrated satisfactory psychometric properties among teachers in Banten Province, cross-validation in other provinces is still needed. Originality/value – The findings provide empirical evidence regarding the reliability of the spiritual competence instrument for madrasah teachers and support its use for both research and assessment purposes.